PENGEMBANGAN PERANGKAT PEMBELAJARAN PBL PADA GOOGLE CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN SPASIAL MATEMATIKA KELAS VIII - Nurul Fathia; Yerizon Yerizon (Universitas PGRI Madiun, 2022)
This study aims to produce learning tools based on problem learning in google classroom that are valid, practical and effective. This research is a development research carried out with the Plomp development model. The Plomp development model consists of three stages, namely the preliminary research phase, the prototyping phase, and the assessment. The subjects of this study were students of class VIII SMPN 1 Rambatan. Validation was carried out by experts in mathematics education, educational technology, and the Indonesian language. The practicality of learning devices is seen from the results of observations, interviews, and student practicality questionnaires. The effectiveness of the learning device can be seen from the results of the students' spatial ability test on the KKM The results of the validity data analysis showed that the problem-based learning tools in Google Classroom to improve the spatial ability of the mathematics produced met the valid criteria in terms of content and construction. Practical learning tools in terms of implementation, convenience and processing time. Learning tools have also been effective, as can be seen from the improvement seen in the results of students' spatial ability tests. Based on these results, it can be said that problem-based learning tools in Google Classroom to improve the spatial ability of the mathematics produced can be declared valid, practical and effective.